Neoantigen: A New Breakthrough in Tumor Immunotherapy - Zhang, Zheying; Lu, Manman; Qin, Yu; Gao, Wuji; Tao, Li; Su, Wei; Zhong, Jiateng (Frontiers in Immunology, 2021)
Cancer immunotherapy works by stimulating and strengthening the body's anti-tumor immune response to eliminating cancer cells. Immunotherapy has shown remarkable efficacy in the treatment of cancer in the past few decades. The success of immune checkpoint blockade targeting CTLA-4, PD-1 and PDL1 has led to a breakthrough in tumor immunotherapy. However, the overall response rate is not high, and only a part of cancer patients benefit. A growing number of studies have highlighted the relationship between neoantigens and T cells' recognition of cancer cells. Tumor neoantigens are abundantly expressed only in tumor cells with strong immunogenicity and tumor heterogeneity. As a new tumor immunotherapy method, vaccines developed for neoantigens have been used in clinical trials of various solid tumors. In this review, we summarized the latest advances in the classification of immunotherapy and the process of classification, identification and synthesis of tumor-specific neoantigens, as well as their role in current cancer immunotherapy. Finally, the application prospects and existing problems of neoantigens were discussed.